Fungsi Pra Penuntutan Terhadap Keberhasilan Pelaksanaan Penuntutan Perkara Pidana Oleh Penuntut Umum - Cakra Nur Budi Hartanto (UNISSULA Semarang, 2017)
The prosecution process of a criminal case conducted by the Public Prosecutor is an estuary from the investigation conducted by the Investigator, but the successful implementation of the prosecution of the criminal case can not be separated from the pre-prosecution role which is also done by the Prosecutor General. Keywords : prosecution, pre-prosecution, prosecutor general